Feasibility study of salt industry and factor influencing the salt production in Pangkajene Kepulauan - Kasnir, Muhammad; Nisaa, Khairun (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
This study aimed to investigate the dissemination level of Ulil Filtered Technology (TUF) and geo-membrane technology and factors influencing salt production in Pangkep. Purposive sampling was performed for data collection. Regression analysis was applied for data analysis. Revenue cost analysis (R-C ratio) was performed. Break Event Point analysis (BEP) was applied, and Pay Back Period (PBP) analysis was used. The results showed that salt farmers unfamiliar with TUF and geo-membrane technology ranged from 6.71 to 9.62%, reasonably know (36.53 - 37.76%) and know to use TUF and geo-membrane technology (53.85 - 55.53%). Cost and technology significantly affected salt production, including area and number of labourers. The business feasibility study showed that Revenue Cost Ratio (1.98), Break Event Point (IDR 4,735,276), and Pay Back Period (1.9 years), respectively.